Native American stories - Bruchac, Joseph; Ka-Hon-Hes, ill.; Caduto, Michael J. Keeprs of the earth (Golden, Colorado : Fulcrum Pub, 1991)
A collection of Native American tales and myths focusing on the relationship between man and nature
" From keepers of the earth [by] Michael J. Caduto and Joseph Bruchac."
Keywords: Indians of North America -- Legends; Indians of North America -- Religion and mythology